(untitled) (Revista Brasileira Multidisciplinar, 2010)
This article aims to contribute to studies on the challenges for the development of small rural communities that seek to reconcile the development of agricultural and non agricultural activities as an important instrument to combat rural poverty, the instability of farm incomes and rural depopulation. The survey was conducted with ranchers installed on the Mogi Guaçu river, located in the town of Barrinha, SP, which has as a peculiar characteristic to be a dormitory town of day laborers who work in sugar cane plantations in the region of Ribeirão Preto / SP. The community is made up of ranches, housing and local production units, where various economic activities - agricultural and non agricultural ones- take place and interact among themselves and with local associations. The theoretical references are based on authors who discuss conditions of formation of the "new Brazilian rural" and "multi-activity in the field", explaining the issue from a paradox between the presence of large estates and monoculture, on one hand, and, on the other hand, of small family farms that develop these activities to remain in the field. The research has showed an experience that does not fit only on studies of pluriactivity in the field but showed the importance of cooperation between ranchers as a form of guarantee of support for their activities and the importance of the role of the public sector as a guarantee of institutional support. In the context of studies of the new countryside, the case study presents an innovative experience practiced by actors who have created a unique form of organization to generate employment and income.